2019
DOI: 10.1002/ajoc.201900329
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐Specific Membrane Antigen (PSMA)‐Targeted Radionuclide Probes for Imaging and Therapy of Prostate Cancer

Abstract: Prostate cancer (PCa) is one of the common cancers among men. Despite the prevalence of PCa, there are still unmet medical needs in the diagnosis and treatment of metastatic prostate cancer. Prostate‐specific membrane antigen (PSMA) is a type II zinc‐dependent metalloprotease which is highly overexpressed in metastatic PCa. In the last several years, PCa imaging probes targeting PSMA have been developed in academia as well as in industry. Among them, low molecular weight PSMA‐targeted ligands based on the Glu‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…Specifically, the well‐known “Lys‐urea‐Glu” moiety was used. This targeting vector, which was prepared by solid‐phase peptide synthesis, [27] has high affinity for the PSMA, a membrane protein that is overexpressed on the surface of various subtypes of prostate cancer cells [28] . The naphthyl and tranexamic acid moieties present in py‐macrodipa‐PSMA, are also employed by the recently FDA‐approved radiotherapeutic [ 177 Lu]Lu 3+ ‐PSMA‐617 (Pluvicto™) [29] and confer additional enhancement to the PSMA target [30] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the well‐known “Lys‐urea‐Glu” moiety was used. This targeting vector, which was prepared by solid‐phase peptide synthesis, [27] has high affinity for the PSMA, a membrane protein that is overexpressed on the surface of various subtypes of prostate cancer cells [28] . The naphthyl and tranexamic acid moieties present in py‐macrodipa‐PSMA, are also employed by the recently FDA‐approved radiotherapeutic [ 177 Lu]Lu 3+ ‐PSMA‐617 (Pluvicto™) [29] and confer additional enhancement to the PSMA target [30] …”
Section: Resultsmentioning
confidence: 99%
“…This targeting vector, which was prepared by solid-phase peptide synthesis, [27] has high affinity for the PSMA, a membrane protein that is overexpressed on the surface of various subtypes of prostate cancer cells. [28] The naphthyl and tranexamic acid moieties present in py-macrodipa-PSMA, are also employed by the recently FDA-approved radiotherapeutic [ 177 Lu]Lu 3 + -PSMA-617 (Pluvicto™) [29] and confer additional enhancement to the PSMA target. [30] With this bioconjugate on hand, we next evaluated its potential use as a radiopharmaceutical agent, via several initial proof-of-principle studies.…”
Section: Resultsmentioning
confidence: 99%
“…It contains a "Lys−urea−Glu" moiety, which targets the prostatespecific membrane antigen (PSMA) that is overexpressed in prostate cancer. 60 In addition, a serum-albumin-binding iodophenyl group was also included to prolong in vivo circulation. 61 Like free macropa, RPS-070 rapidly incorporated 225 Ac 3+ within 20 min at RT and pH 5−5.5, demonstrating that the newly introduced biomolecule does not negatively affect the coordination properties of this ligand.…”
Section: Development Of Macropa-basedmentioning
confidence: 99%
“…Macropa-NCS was then successfully conjugated to a small molecule, giving a bioconjugate RPS-070 (Chart b). It contains a “Lys–urea–Glu” moiety, which targets the prostate-specific membrane antigen (PSMA) that is overexpressed in prostate cancer . In addition, a serum-albumin-binding iodophenyl group was also included to prolong in vivo circulation .…”
Section: Development Of Macropa-based Bifunctional Chelators and Bioc...mentioning
confidence: 99%
“…In particular, the structural freedom provided by the S1 site allows diverse structural modifications to PSMA inhibitors. ,, Since the pioneering work by Kozikowski and colleagues, the most common scaffold of PSMA inhibitors is a lysine–urea–glutamate (Lys–urea–Glu) motif that has a high binding affinity and specificity for PSMA despite the diverse structural variation in the P1 site. The ε-amine group of lysine in Lys–urea–Glu has been conjugated with a variety of imaging prosthetic groups and diverse linkers. Some excellent and comprehensive recent reviews on PSMA-targeted imaging probes derived from the Lys–urea–Glu motifs were reported. …”
Section: Introductionmentioning
confidence: 99%